Producing, reproducing the common. Rural womenof Bañado de los Pantanos, La Rioja (La Rivada, 2025)
This paper is based on the Río Colorado project: an ethnography of water, carried out by an interdisciplinary team where social work intersects, based on specific dialogues and approaches. It also follows Freire's action research methodology, with active listening being a fundamental component in the complexity of possible outcomes. The territory where the proposal is being carried out is the town of Bañado de los Pantanos, Arauco Department, La Rioja. This locality was chosen because it is considered to be a manifestation of the population's roots and deep -rootedness, as it is a community that has settled generation after generation in the same space-territory-land. The aim is to record and systematize an ancestral production practice. In the process, it became clear that the interpretative locus had to be re-inscribed from the community's perspective.
Keywords: Rural women; borders of capital; reproduction of the common; social work